2016
DOI: 10.1038/cdd.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to bisphenol A or benzo(a)pyrene alters the fate of human mammary epithelial stem cells in response to BMP2 and BMP4, by pre-activating BMP signaling

Abstract: Bone morphogenetic protein 2 (BMP2) and BMP4 are key regulators of the fate and differentiation of human mammary epithelial stem cells (SCs), as well as of their niches, and are involved in breast cancer development. We established that MCF10A immature mammary epithelial cells reliably reproduce the BMP response that we previously identified in human primary epithelial SCs. In this model, we observed that BMP2 promotes luminal progenitor commitment and expansion, whereas BMP4 prevents lineage differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…The behaviour of stem cells can be influenced by different environmental factors (Shaw et al ., ). Particularly, previous studies have shown that BMP4 can increase the number of mammospheres generated by MCF10A cells (Clément et al ., ). When both HDAC7 +/+ and HDAC7 −/− cells were treated with BMP4, the number of spheres was augmented.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The behaviour of stem cells can be influenced by different environmental factors (Shaw et al ., ). Particularly, previous studies have shown that BMP4 can increase the number of mammospheres generated by MCF10A cells (Clément et al ., ). When both HDAC7 +/+ and HDAC7 −/− cells were treated with BMP4, the number of spheres was augmented.…”
Section: Resultsmentioning
confidence: 97%
“…A,B). The combination of the surface markers CD44 + /CD24 low was used to distinguish stem‐like cells (Amin et al ., ; Clément et al ., ; Shaw et al ., ). We did not observe such a reduction of this population in HDAC7 −/− cells, to justify the failure in the mammosphere assay (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, chronic long-term exposure to high levels of soluble BMP2 could initiate the luminal transformation of predisposed breast epithelial stem cells through binding to BMPR1b (5). In addition, environmental pollutants such as estrogeno-mimetic bisphenols, are able to initiate deregulations of the BMP signaling by altering BMP pathway members expression within epithelial stem cells, as well as BMP expression itself by their microenvironment (5,17). In this context, it is interesting to observe an absence of induced tumorigenesis after long-term dual TGF-β and BMP pathways inhibition in primary epithelial stem cells.…”
Section: Commentarymentioning
confidence: 99%